Aplicação da simulação de Monte Carlo no valuation da empresa Engie Brasil Energia - Pinto, Gabriel (Universidade Estadual Paulista (Unesp), 2022)
Valuation is the process of calculating the value of an asset, being applied in determining the value of stocks, portfolio management, merger and acquisition process, etc. In this paper, the Discounted Cash Flow (DCF) method was employed, which calculates the intrinsic value of an asset, based on assumptions related to cash flow projections. In order to capture the uncertainties related to these assumptions, the Monte Carlo Simulation (MCS) was incorporated into the model, being performed a comparative analysis between the results obtained in the DCF model and the results of the model that incorporates the MCS in the DCF. For the adoption of premises, a study was held about the electric sector and the evaluated company, Engie Brasil Energia, the largest private electric power generator company in Brazil in 2022. Excel and the VBA programming language were used in the modeling, and the data were obtained from the Engie Brasil Energia website. With the DCF, a valuation of 44.17 BRL per share was calculated, and by incorporating MCS into the DCF, a probability distribution of the value per share was obtained with an average value of 43.78 BRL. It was concluded that by applying the MCS to the DCF, a more comprehensive view of the company's value is achieved by considering the impact of the uncertainties of the assumptions

O valuation é o processo de calcular o valor de um ativo, sendo aplicado na determinação do valor de ações, gestão de portfólio, processo de fusão e aquisição, etc. Neste trabalho utilizou-se o método do Fluxo de Caixa Descontado (FCD) que calcula o valor intrínseco de um ativo baseando-se em premissas relativas às projeções de fluxos de caixa. Para capturar as incertezas relativas a estas premissas incorporou-se a Simulação de Monte Carlo (SMC) ao modelo, sendo realizada uma análise comparativa dos resultados obtidos no modelo FCD e dos resultados do modelo que incorpora a SMC ao FCD. Para a adoção de premissas realizou-se um estudo do setor elétrico e da empresa avaliada, Engie Brasil Energia, a maior geradora privada de energia elétrica no Brasil em 2022. Na modelagem utilizou-se o Excel e a linguagem de programação VBA, sendo os dados utilizados obtidos no site da Engie Brasil Energia. Com o FCD calculou-se um valuation de R$44,17 por ação e ao incorporar a SMC ao FCD obteve-se uma distribuição de probabilidade do valor por ação com valor médio de R$43,78. Concluiu-se que ao aplicar a SMC ao FCD obtém-se uma visão mais abrangente do valor da empresa ao considerar o impacto das incertezas das premissas.
Application of Monte Carlo simulation in the valuation of the Engie Brasil Energia company
Keywords: Discounted Cash Flow; Monte Carlo Simulation; Valuation; Fluxo de caixa descontado; Simulação de Monte Carlo; Monte Carlo, Método de; Fluxo de caixa; Ações (Finanças)